2016
DOI: 10.1021/acscombsci.5b00139
|View full text |Cite
|
Sign up to set email alerts
|

A High Performance Platform Based on cDNA Display for Efficient Synthesis of Protein Fusions and Accelerated Directed Evolution

Abstract: We describe a high performance platform based on cDNA display technology by developing a new modified puromycin linker-oligonucleotide. The linker consists of four major characteristics: a "ligation site" for hybridization and ligation of mRNA by T4 RNA ligase, a "puromycin arm" for covalent linkage of the protein, a "polyadenosine site" for a longer puromycin arm and purification of protein fusions (optional) using oligo-dT matrices, and a "reverse transcription site" for the formation of stable cDNA protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Next, various salt mix concentrations were tested during post translation incubation. Previously, a high concentration of KCl has been shown to improve the accessibility of ribosomebound peptidyl-tRNA to puromycin (Van Der Mast & Bloemers, 1973) and has been adopted in the recent mRNA and cDNA display methods (Naimuddin & Kubo, 2016;Seelig, 2011;Yamaguchi et al, 2009). We found that without salt addition, conjugate formation is less than 10%, however the addition of 32.5 mM MgCl 2 and 375 mM KCl greatly increased the formation rate to above 40% ( Figure 2B).…”
Section: Optimization Of Conjugate Formation During In Vitrotranslationmentioning
confidence: 69%
See 4 more Smart Citations
“…Next, various salt mix concentrations were tested during post translation incubation. Previously, a high concentration of KCl has been shown to improve the accessibility of ribosomebound peptidyl-tRNA to puromycin (Van Der Mast & Bloemers, 1973) and has been adopted in the recent mRNA and cDNA display methods (Naimuddin & Kubo, 2016;Seelig, 2011;Yamaguchi et al, 2009). We found that without salt addition, conjugate formation is less than 10%, however the addition of 32.5 mM MgCl 2 and 375 mM KCl greatly increased the formation rate to above 40% ( Figure 2B).…”
Section: Optimization Of Conjugate Formation During In Vitrotranslationmentioning
confidence: 69%
“…For the translation time, we tested 0, 5, 15, 30 and 60 minutes at 37 , prior to the addition of salt mix (final conc, 32.5 mM MgCl 2 and 375 mM KCl) followed by 60 minutes of incubation. For the optimization of salt mix concentration, we first conducted 30 minutes translation at 37 , then either added no salt or 1x, 1/2x, 1/4x, 1/8x concentration of 65 mM MgCl 2 and 750 mM KCl concentration originally reported to promote covalent bond between puromycin and polypeptide chain (Naimuddin et al, 2011;Naimuddin & Kubo, 2016). For the incubation time after salt addition, we initially performed 30 minutes translation, added salt to final 32.5 mM MgCl 2 , 375 mM KCl concentration, then tested 0, 10, 30, 60 and 90 minutes of incubation time.…”
Section: Optimization Of Mrna-peptide Conjugate Formationmentioning
confidence: 99%
See 3 more Smart Citations